Security, insecurity and health - Robin Coupland
An examination of the nexus of security, insecurity and health shows that security is a prerequisite for health. The many and varied ways that armed violence - including threats of armed violence - can affect people's health can be documented by formal studies; however, valuable data also exist in other reports, such as media reports. The health community needs to recognize that people's insecurity is a massive global health issue. The foreign policies of donor governments should incorporate recognition that documentation, analysis and publication of data describing the impact of insecurity on people's health can lead to the creation of policies to enhance people's security.